Rossica w kwartalniku kulturalnym „Opcje” (1993-2010) - Pawletko, Beata (Acta Polono-Ruthenica, 2010)
The cultural magazune Opcje is a periodical devoted to the culture. Opcje brings up important phenomena of literature, music, art, philosophy, theater and movie. The present paper presents a review of magazines content from the perspective of works concerning Russian culture and literature. It turned out that subjects connected with Russia are quiet often discussed in the magazine Opcje. Readers can find here not only descriptions of Russian literature and reviews of its translations into Polish language, but also papers dedicated to the Russian filmmaking, music and theater.